Exploring Junior High School Students’ Critical Thinking Processes in Problem Posing on Systems of Linear Equations in Two Variables Using GeoGebra - Fidyah Maulidah; Tatag Yuli Eko Siswono (Journal of the Indonesian Mathematics Education Society, 2026)
This study aims to explore the critical thinking processes of junior high school students in posing, modifying, and validating problems involving Systems of Linear Equations in Two Variables with the support of GeoGebra. Using Ennis’s (2022) theoretical framework, the study analyzes six indicators of critical thinking: focus, reasoning, inference, contextual understanding, clarity, and overview. A qualitative descriptive case study method was employed with three eighth-grade students of varying mathematical abilities (high, medium, and low). Data were collected through a problem-posing test, observation of GeoGebra use, and semi-structured interviews. The results indicate that the high-ability student (S1) was able to appropriately modify Systems of Linear Equations in Two Variables problems with strong mathematical reasoning, supported by GeoGebra visualizations. The medium-ability student (S2) was able to change parameters but had limited understanding of the implications of those changes on the solution. Meanwhile, the low-ability student (S3) struggled to modify problems and validate solutions, even producing inconsistent systems. These findings highlight the critical role of GeoGebra in facilitating conceptual understanding of Systems of Linear Equations in Two Variables while also identifying challenges faced by students with different levels of mathematical ability. The study offers pedagogical implications for the development of technology-integrated mathematics instruction aimed at enhancing students’ critical thinking skills.